2020
DOI: 10.3390/nu12040937
|View full text |Cite
|
Sign up to set email alerts
|

Randomised Double-Blind Placebo-Controlled Trial of Inulin with Metronidazole in Non-Alcoholic Fatty Liver Disease (NAFLD)

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) can be ameliorated by weight loss although difficult to maintain. Emerging evidence indicates that prebiotics and antibiotics improve NAFLD. Aim: To determine whether inulin supplementation after brief metronidazole therapy is effective in reducing alanine aminotransferase (ALT) and maintaining weight loss achieved through a very-low-calorie diet (VLCD) among people with NAFLD. Methods: Sixty-two people with NAFLD commenced 4-week VLCD using Optifast meal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…It can be fermented by gut bacteria to produce butyrate. Chong et al (2020) reported that supplementation of inulin further reduced ALT induced by metronidazole in a randomized double-blind placebo-controlled clinical trial [ 99 ]. Weitkunat et al (2015) reported that inulin feeding to mice increased production of SCFAs and reduced expression of genes involved in lipogenesis and fatty acid elongation/desaturation [ 100 ].…”
Section: Modulation Of Gut Microbiota and Its Metabolitesmentioning
confidence: 99%
“…It can be fermented by gut bacteria to produce butyrate. Chong et al (2020) reported that supplementation of inulin further reduced ALT induced by metronidazole in a randomized double-blind placebo-controlled clinical trial [ 99 ]. Weitkunat et al (2015) reported that inulin feeding to mice increased production of SCFAs and reduced expression of genes involved in lipogenesis and fatty acid elongation/desaturation [ 100 ].…”
Section: Modulation Of Gut Microbiota and Its Metabolitesmentioning
confidence: 99%
“…Rifaximin, a broad spectrum antibiotic, lowered ALT levels, endotoxemia and HOMA-IR in histologically-diagnosed obese NASH patients [152]. Treatment combining metrodinazole, an antiprotozoal antibiotic, and the prebiotic inulin decreased transaminase levels in prediabetic patients, an effect not observed with inulin alone [153]. The lack of bacterial species-selective antibiotics and the apparition of antibiotic resistance strongly limit the use of antibiotics for metabolic disorders, which should be restricted to infections.…”
Section: Targeting Microbiotamentioning
confidence: 99%
“…In a clinical study, inulin, an important kind of prebiotics, was shown to decrease hepatic lipogenesis and plasma triglyceride level ( Letexier et al, 2003 ). Another double-blind, placebo-controlled trial also showed that metronidazole with inulin supplementation can reduce ALT beyond that achieved after very-low-calorie diet in patients with NAFLD ( Chong et al, 2020 ). However, generally speaking, the results are inconsistent.…”
Section: The Microbial Metabolites As a Potential Therapeutic Target mentioning
confidence: 99%